Evaluación del desempeño docente de la escuela de comercio exterior y negociación comercial internacional (ECEYNCI) "Período académico septiembre 2012- agosto 2013" - Carvajal Pérez, Luis Alfredo; Realpe Delgado, Ofelia Beatriz; Solórzano Robinson, Hada Esther (Tierra Infinita, 2015)
The evaluation of teaching performance at the State Polytechnic University of Carchi (UPEC) and specifically in Foreign Trade and International Trade Negotiations School's (ECEYNCI), is a process framed in compliance with Articles 151 and 155 of the LOES that refer to that the teachers are subjected to periodic comprehensive evaluation on the based on Regulation of Racing and category Professor and Researcher of Higher Education System including student participation in the assessment. For this has established a biannual assessment considering the following components: Assessment of student to teachers (EED), Self evaluation (A), Evaluation of the management of school to teachers (EDD) and peer evaluation (PPE).The average assessment in Total for the period March 2013 - August 2013, of the teachers of ECEYNCI is higher to 80%, with an opportunity of improvement to achieve the following competencies: development of conscious knowledge, developing conscious attitudes development of abilities and skills, developing the ability to investigate and evaluate learning.